Canadian Paediatric Neurology Workforce survey and consensus statement. (3rd June 2015) - Doja, A; Orr, S; McMillan, H; Kirton, A; Callen, D
Abstract : Background: Little knowledge exists on the availability of paediatric neurology positions. Our study aimed to: 1) obtain information regarding the availability of positions for paediatric neurologists in academic centres; 2) survey paediatric neurology trainees regarding their perceptions of employment issues and career plans; 3) survey practicing community paediatric neurologists 4) convene a group of paediatric neurologists to develop a consensus regarding how to address these workforce issues. Methods: Surveys addressing workforce issues regarding paediatric neurology in Canada were sent to: 1) all paediatric neurology program directors in Canada who then solicited information from division heads and from paediatric neurologists in surrounding areas; 2) paediatric neurology trainees in Canada and; 3) community paediatric neurologists. A meeting was held with relevant stakeholders to develop a consensus on how to approach employment issues. Results: We found that the number of projected positions in academic paediatric neurology is fewer than the number of paediatric neurologists that are being trained. Paediatric neurology residents are concerned about job availability and desire more career counselling. Conclusions: There is a current and projected clinical demand for paediatric neurologists despite a lack of academic positions. Training programs should focus on community neurology as a viable career option.